A rare case report of giant de novo cervical cystic hygroma in an elderly patient: Case report. (April 2021) - Hammed, Salah; Al Assaf, Areeg; Hammed, Ali; Saker, Ziad; Dway, Ali
Abstract: Introduction and importance: Cystic hygroma is an aberrant proliferation of lymphatic vessels resulting from abnormal development of the lymphatic system. Cervical lymphangioma is an uncommon entity, usually reported in children, rarely in adult. Case presentation: Our case presents a 65-year-old man with an extremely huge right-sided painless cervical swelling since 8 years with no symptoms. Clinical discussion: Computer tomography (CT) showed a cystic lesion with thin walls of 150 × 100mm, medial to right sternocleidomastoid muscle (SCM). The lesion was completely resected along with the entire capsule. Post-operatively, the patient recovered well with no signs of any neurological dysfunction and he was discharged from hospital after 2 days. Conclusion: The etiology in the adult population is controversial. Diagnosis in adults is considered to present a greater challenge than in children, and final diagnosis is usually based on postoperative histology. Cystic hygroma should be considered as a differential diagnosis of cervical masses in adults.